2014
DOI: 10.1002/rra.2748
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Intermittent Stream Fish Assemblages to Irrigation Development

Abstract: Large-scale irrigation projects are being undertaken in the Mediterranean region, and agricultural practices are being intensified, but their impacts on instream biota remain poorly documented. The present study assesses the effects of an irrigation scheme on fish community structure in Mediterranean streams. Fish assemblages were sampled in unregulated intermittent streams over 6 years concurrently with the development of a new irrigation project in southwestern Iberia, and the biotic variation was separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…These dynamic systems present numerous challenges for scientific research, monitoring, management, societal valuation and setting of policy goals. Papers in this Special Issue embrace these challenges with vigour and innovation through consideration of patterns of biodiversity and ecohydrology (Balcombe et al, 2014;Leitão et al, 2014;Novais et al, in press;Pires et al, 2014), impacts of impoundment, flow regulation and agricultural intensification (Godinho et al, 2014;Matono et al, 2014), community composition and biotic interactions involving alien species (Bueno-Enciso et al, 2014;Magoulick, 2014), ecological condition (health) assessment (Prat et al, 2014) and the concept and practice of reconciliation ecology (Moyle, 2014) as a way of managing novel ecosystems for their values and desirable ecological services to society, rather than trying to restore an unachievable original ecological state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dynamic systems present numerous challenges for scientific research, monitoring, management, societal valuation and setting of policy goals. Papers in this Special Issue embrace these challenges with vigour and innovation through consideration of patterns of biodiversity and ecohydrology (Balcombe et al, 2014;Leitão et al, 2014;Novais et al, in press;Pires et al, 2014), impacts of impoundment, flow regulation and agricultural intensification (Godinho et al, 2014;Matono et al, 2014), community composition and biotic interactions involving alien species (Bueno-Enciso et al, 2014;Magoulick, 2014), ecological condition (health) assessment (Prat et al, 2014) and the concept and practice of reconciliation ecology (Moyle, 2014) as a way of managing novel ecosystems for their values and desirable ecological services to society, rather than trying to restore an unachievable original ecological state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple natural and anthropogenic stressors complicate the identification of fish community metrics responsive to specific human pressures (Hermoso et al, 2010). Nevertheless, Godinho et al (2014) identified a series of fish community metrics clearly indicating changes associated with impoundment and irrigation intensification within intermittent streams of southwestern Iberia. The proportion of less tolerant species and native invertivores was found to decrease with increasing levels of irrigation, while most introduced species increased in their relative abundance with an increasing area of irrigated land in the catchment.…”
Section: Synthesis Of Papersmentioning
confidence: 99%
“…Downstream of dams, the impacts are manifold, including sediment depletion and rearrangement of the biogeomorphological stream components [6][7][8][9]. Several studies showed that the reduction of water flow and sediment downstream of the dam promotes changes in distinct biological communities, such as fish and invertebrates (e.g., [10][11][12]). The modification of the natural hydrologic regime depends on the technical characteristics of dams and on their operation rules and impacts the aquatic and riparian ecosystems differently in composition and spatial distribution [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the impact of drought will be exacerbated by human-induced flow alteration, which may lessen the resilience of fish communities to hydrologic change (Matono et al 2014;Bunn & Arthington 2002). Thus, fish communities are anticipated to respond in complex ways to the potential interactive effects of drought and flow alteration (and, likely, other stressors) in Mediterranean-type temporary streams (Boix et al 2010;Matono et al 2012Matono et al , 2014Godinho et al 2014).…”
Section: Introductionmentioning
confidence: 99%